Growth profile of Bacteroidetes strains under low molecular weight alginate fractions produced by non-thermal processing techniques - Pedro Rivero-Ramos; Pedro J. Fernandez-Julia; Dolores Rodrigo; María Benlloch-Tinoco; Jose Munoz-Munoz (Food Hydrocolloids for Health)
Alginate is a dietary polysaccharide that is known to support the growth of particular gut-associated bacteria, including members of the Bacteroides genus. However, there is limited understanding of how key physicochemical characteristics of partially depolymerised alginate fractions affect the growth of various Bacteroidetes strains. In this study, the growth profile of Bacteroides thetaiotaomicron VPI-5482, Bacteroides cellulosilyticus WH2 and Dysgonomonas mossii DSMZ22836 on alginate fractions (Mw = 17–58 kDa) with different mannuronic and guluronic ratios (M/G ratio = 0.27–1.14) depolymerised by high hydrostatic pressures (HHP), pulsed electric fields (PEF) and H2O2-based treatments was screened. The tested strains were able to grow in the HHP, PEF and H2O2 treated samples. Growth of Bacteroides sp. was significantly affected by the physicochemical properties of the alginate substrates. The lower the Mw of the samples the faster the growth for the three strains investigated (p < 0.05, r = −0.7757). Higher M/G ratios significantly enhanced the growth of B. thetaiotaomicron VPI-5482 (p < 0.05, r = 0.9685). Finally, D. mossii DSMZ22836 was found to employ three enzymes (Aly, GH88, GH92) to degrade the low Mw alginate fractions. This study advances the understanding of strain-specific interactions of three glycan degraders in the presence of various low Mw alginate fractions.